Assessing Social Cognition of Persons with Schizophrenia in a Chinese Population: A Pilot Study - Lo, Panmi M. T.; Siu, Andrew M. H. (Frontiers in Psychiatry, 2018)
Social cognition is a core limiting factor of functional recovery among persons with schizophrenia. However, there is a lack of standardized and culturally relevant assessment tools for evaluating social cognitive performance in Chinese persons with schizophrenia. The purposes of this study were to 1) develop and validate two social cognitive instruments, the Chinese Facial Emotion Identification Test (C-FEIT) and the Chinese Social Cognition and Screening Questionnaire (C-SCSQ), that assess three key domains of social cognition; and 2) to evaluate preliminary psychometric properties of the two assessments. The results demonstrated that the C-FEIT and the social cognitive subscales of C-SCSQ possess satisfactory content-related validity and test-retest reliability (ICC ranging from .76 to .85). Subscales of the C-FEIT and the C-SCSQ showed low to medium correlation with two concurrent neurocognitive measures (absolute values of r ranging from .22 to .45) and concurrent measures of functional performance (absolute values of r ranging from .22 to .46). Our findings generally support the use of the C-FEIT and the C-SCSQ as reliable and valid tools for assessing emotion perception, theory of mind (intention-inferencing), and hostile attributional style, which are the key outcome indicators of social cognitive interventions for persons with schizophrenia.